Global trade policy : questions and answers - Smith, Pamela J. (Wiley Blackwell, 2014)
Using a unique, question-based format, Global Trade Policy offers accessible coverage of the key questions in trade and policy; it charts the changing policy landscape and evolving institutional arrangements for trade policies, examines trade theory, and provides students with an economic framework to better understand the current issues in national and international trade policy. Uses a unique, question-based format to explore the questions and current debates in international trade policy and their implicationsExplores trade theory to help guide discussions of trade po.